Productivity of a collection Solanum tuberosum varieties in the conditions of the Northern Trans-Urals - Rodina Ekaterina S.; Reneva Mariya V.; Renev Nikolay O.; Timofeev Vyacheslav N. (BIO Web of Conferences)
Research to evaluate the collection of Solanum tuberosum varieties was carried out in the conditions of 2023, the Northern forest-steppe zone of the Tyumen region. In the collection, 49 varieties of different ripeness groups were studied, the varieties are represented by different geographies of origin of Russian and foreign breeding centers. Potato varieties differ significantly from each other in phenological indicators; among the early varieties, upon the onset of full budding, the varieties Colombo, Lyubava, Isetsky, and Antonina stood out. In the mid-early group, the budding phase began 9-11 days earlier in the varieties Stepana, Svitanok Kyiv, Nevsky, Adretta, Ausonia, Belmando, Sineglazka, Arnika, and Lily. Among the mid-season varieties Otrada and Sokur, the budding phase began 8 days earlier than the standard (Tuleevsky variety). The onset of phenological phases with a delay in relation to the control in early-ripening varieties was 6-58%, in mid-early varieties 4.5-18%, and in mid-ripening varieties up to 10%. In terms of yield in the early ripening group, the varieties Labella (27.41 ‒ 37.49 t/ha) and Colombo (28.64 ‒ 38.60 t/ha) were higher than the standard variety Zhukovsky (26.74 ‒ 35.65 t/ha). In the mid-early period, the following varieties distinguished themselves in yield: Arnika (33.84 t/ha), Banba (30.07 t/ha), Adretta (29.19 t/ha), Sarma (29.02 t/ha). As a result, varieties were identified that showed an increase in yield in conditions of a year with a lack of moisture, exceeding the standard in the early-ripening group of 11% of varieties, and in the mid-early and mid-ripening groups of 44% of varieties.